Severed stems of Amaranthus palmeri are capable of regrowth and seed production in Gossypium hirsutum. (22nd April 2014) - Sosnoskie, L.M.; Webster, T.M.; Grey, T.L.; Culpepper, A.S.
Abstract Field studies were conducted to evaluate the capacity of Amaranthus palmeri to grow and reproduce following incomplete physical control in Gossypium hirsutum fields. A. palmeri plants that emerged simultaneously with a G. hirsutum crop were selected for use. Treatments included severing the main stem of flowering plants at heights of 0, 3 and 15 cm above the soil level. A non‐cut/intact control, in which the apical meristem was not removed, was also included. Six weeks after treatment, intact A. palmeri plants had grown to a mean height of 210 cm (SE = 38) and produced 477 408 (SE = 81 250) seeds per plant. Thirty‐five percent of the A. palmeri plants cut back to a height of 15 cm above the soil level did not recover from the treatment; survivors regrew to a mean height of 102 cm (51% reduction, compared to intact plants) and produced 116 000 seeds per plant (73% reduction). A. palmeri plants cut to 3 cm above the soil level had a mortality rate of 64%, an 82% reduction in final plant height, and produced 28 000 seeds per plant. When stems were severed at the soil surface, plant mortality was 95%; final plant height and seed production of survivors were reduced by 95 and 99%, respectively, relative to the control. G. hirsutum seeded yields exceeded 3 t ha−1 when A. palmeri plants were cut back to at least 15 cm, whereas yield was reduced 50% in the control treatment, where A. palmeri growth was not interrupted by cutting. In conclusion, while there is immediate benefit of removing A. palmeri plants in terms of G. hirsutum yield, incomplete stem removal can have multi‐season implications. Results demonstrate that severely pruned A. palmeri plants can resume growth, reach reproductive maturity and produce viable seed, which have the potential to repopulate soil seedbanks.